2007
DOI: 10.1111/j.1365-2249.2007.03457.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in chemokine receptor genes and susceptibility to Kawasaki disease

Abstract: SummaryKawasaki disease (KD) is an acute vasculitis occurring in young children. Its aetiology is unknown, but an infectious agent is assumed. Increased levels of proinflammatory cytokines and chemokines have been reported in KD. Genetic variation in these genes and the receptors for these genes could influence the regulation of cytokines and chemokines. In a case-control study of 170 Dutch Caucasian KD patients and 300 healthy Dutch Caucasian controls, common genetic variants in chemokine receptor genes CCR3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
3
27
0
2
Order By: Relevance
“…30 Although several other groups have studied other combinations of HLA subtypes, no consistent association has been detected so far. Considering that no significant linkage was detected near the 6p region in our genome-wide linkage analysis, 31 34 and MCP-1 35 ), hematopoietins (interleukin-4 (IL-4) [36][37][38] and IL-6 39 ), IL-1 family (IL-1b, 37 IL-18, 40 and IL-1Ra 37 ), IL-10 family (IL-10 41 ), platelet-derived growth factor family (vascular endothelial growth factor (VEGF) [42][43][44][45] and VEGFR2 42 ), and tumor necrosis factor (TNF) family (TNF-a, 46-50 lipoteichoic acid, 47 and CD40L 51,52 ). Other candidates include plasma proteins (C-reactive protein [53][54][55] and MBL2 53,55,56 ), matrix metalloproteinase (MMP) and their inhibitors (MMP2, 58 MMP3, 57,58 MMP-9, 58 MMP-12, 58 MMP-13, 58 and tissue inhibitors of metalloproteinase-2 59 ), enzymes related to atherosclerosis (methylenetetrahydrofolate reductase (MTHFR), 60 endothelial nitric oxide synthase, 61 and inducible nitric oxide synthase 61 ), components of the renin-angiotensin system (angiotensin-converting enzyme [62][63][64][65] and AGTR1 64 ), and an unclassified group (CD14, 66 FCGR2A, 67,68 SLC11A1, 69 PLA2G7, 70 UGT1A1, 71 MICA, 72 and HMOX1 71 ).…”
Section: Candidate Gene Approachmentioning
confidence: 81%
“…30 Although several other groups have studied other combinations of HLA subtypes, no consistent association has been detected so far. Considering that no significant linkage was detected near the 6p region in our genome-wide linkage analysis, 31 34 and MCP-1 35 ), hematopoietins (interleukin-4 (IL-4) [36][37][38] and IL-6 39 ), IL-1 family (IL-1b, 37 IL-18, 40 and IL-1Ra 37 ), IL-10 family (IL-10 41 ), platelet-derived growth factor family (vascular endothelial growth factor (VEGF) [42][43][44][45] and VEGFR2 42 ), and tumor necrosis factor (TNF) family (TNF-a, 46-50 lipoteichoic acid, 47 and CD40L 51,52 ). Other candidates include plasma proteins (C-reactive protein [53][54][55] and MBL2 53,55,56 ), matrix metalloproteinase (MMP) and their inhibitors (MMP2, 58 MMP3, 57,58 MMP-9, 58 MMP-12, 58 MMP-13, 58 and tissue inhibitors of metalloproteinase-2 59 ), enzymes related to atherosclerosis (methylenetetrahydrofolate reductase (MTHFR), 60 endothelial nitric oxide synthase, 61 and inducible nitric oxide synthase 61 ), components of the renin-angiotensin system (angiotensin-converting enzyme [62][63][64][65] and AGTR1 64 ), and an unclassified group (CD14, 66 FCGR2A, 67,68 SLC11A1, 69 PLA2G7, 70 UGT1A1, 71 MICA, 72 and HMOX1 71 ).…”
Section: Candidate Gene Approachmentioning
confidence: 81%
“…Previous studies have reported an association between the SNPs occurring in chemokine genes and autoimmune diseases, including systemic lupus erythematosus (SLE) (Brown et al, 2007;Im et al, 2014), Sjögren syndrome (Kahlmann et al, 2007), Kawasaki disease (KD) (Breunis et al, 2007;Jhang et al, 2009), and rheumatoid arthritis (RA) (Zapico et al, 2000;Teng et al, 2012). Brown et al (2007) revealed that the G allele of the -2518A/G SNP in the CCL2 gene significantly increased the risk of SLE among Caucasians, but not among African Americans (P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Ein Polymorphismus im CCChemo kinrezeptor 5 (CCR5) und/oder seinem Liganden CCL3L1 scheint die Suszeptibi lität für KS zu beeinflussen, so gibt es Hin weise darauf, dass die Rekrutierung von Entzündungszellen beim KS durch CCR5 vermittelt werden könnte [4,5,17]. Abge sehen vom hohen Vorkommen der CCR5 δ32Deletion in vielen nordeuropäischen Ländern und besonders in Dänemark [5,26] gibt es keine plausiblen Erklärungen für die Inzidenzunterschiede innerhalb der europäischen Länder sowie zwischen Europa und den USA.…”
Section: äTiologie Des Ksunclassified